2002
DOI: 10.1161/hs0102.101262
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Improving the Quality of Care Through Stroke Centers and Systems: An Examination of Stroke Center Identification Options

Abstract: Identification of stroke centers and stroke systems competencies is in the best interest of stroke patients in the United States, and ASA should support the development and implementation of such processes. The purpose of a stroke center/systems identification program is to increase the capacity for all hospitals to treat stroke patients according to standards of care, recognizing that levels of involvement will vary according to the resources of hospitals and systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…8,11,15 Any PSC certification program should fulfill several criteria to ensure the accuracy and rigor of such programs; these include (1) the certifying body should be administratively and financially independent of the hospital; (2) the program should include an assessment of infrastructure, personnel, protocols, and programs; (3) a site visit should be performed at least every 2 years; and (4) well-defined and quantifiable disease performance measures should be developed and assessed on a regular basis. 15 Self-certification programs are discouraged based on prior studies showing that such efforts often produce unreliable results. 149 The inclusion of specific recommendations for certification is new and is supported by Class 1, Level B evidence.…”
Section: Stroke Center Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,15 Any PSC certification program should fulfill several criteria to ensure the accuracy and rigor of such programs; these include (1) the certifying body should be administratively and financially independent of the hospital; (2) the program should include an assessment of infrastructure, personnel, protocols, and programs; (3) a site visit should be performed at least every 2 years; and (4) well-defined and quantifiable disease performance measures should be developed and assessed on a regular basis. 15 Self-certification programs are discouraged based on prior studies showing that such efforts often produce unreliable results. 149 The inclusion of specific recommendations for certification is new and is supported by Class 1, Level B evidence.…”
Section: Stroke Center Certificationmentioning
confidence: 99%
“…12 Since the initial publication of the PSC recommendations in 2000, there have been substantive modifications and changes in how patients with stroke are diagnosed and treated. [13][14][15][16] These relate to the efficacy and importance of stroke teams, Stroke Units, the use of intravenous tissue plasminogen activator (tPA), and imaging advances, among others. Some other important advances such as endovascular therapies and acute surgery are more germane to a CSC and are not reviewed here.…”
mentioning
confidence: 99%
“…[1][2][3][4] Studies assessing the impact of PSC certification have focused on process measures [5][6][7][8] ; information on outcomes is limited. One study found hospitals receiving JC PSC certification within the first few years of the program had lower 30-day mortality and readmission rates than hospitals without certified centers before the program began, suggesting that they already used processes that led to better stroke outcomes.…”
mentioning
confidence: 99%
“…19 Outlying and community hospitals should develop access via telemedicine or other means to endovascular acute stroke therapy through the development of stroke systems of care if comprehensive stroke center capabilities are not available. 20 The interventionalist must have 24/7 access to neurologists and neurosurgeons knowledgeable in patient selection and in the pre-and postneurologic critical care of endovascularly treated stroke patients.…”
Section: Maintenance Of Physician and Facility Qualificationsmentioning
confidence: 99%